2008
DOI: 10.1016/j.ijid.2007.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of linezolid in the treatment of mediastinitis due to methicillin-resistant Staphylococcus aureus: an experimental study

Abstract: A high dose of linezolid should be considered as a possible therapeutic agent for the treatment of post-sternotomy infection caused by MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In this study, we used previously applied experimental rat mediastinitis models [ 18 , 19 ] . When the literature was examined, we found several animal models using tigecycline, vancomycin and HBO against MRSA, so we aimed to use these antibiotics and HBO.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used previously applied experimental rat mediastinitis models [ 18 , 19 ] . When the literature was examined, we found several animal models using tigecycline, vancomycin and HBO against MRSA, so we aimed to use these antibiotics and HBO.…”
Section: Discussionmentioning
confidence: 99%
“…We used vancomycin, teicoplanin, and linezolid as they were utilized in the treatment of serious infections due to methicillin resistant staphylococci in experimental animal models [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of linezolid in 50 or 100 mg/kg/d in a rat model of pneumococcal pneumonia was also evaluated, and the latter was found to be more effective [34]. We have previously shown that the standard dose mimicking therapeutic dose given to humans was not effective in reducing bacterial count in mediastinum and sternum, but the double dose was [35]. As linezolid is not investigated enough in cardiovascular infections, and as there are reports of treatment failure of another serious cardiovascular infection, endocarditis, with a standard dose used in humans [36], and as our MRSA strain was less susceptible in vitro, we decided to investigate the efficacy of a double dose in mediastinitis, which was previously reported to be effective in the treatment of serious infections and to compare it with vancomycin.…”
Section: Discussionmentioning
confidence: 99%